DOP050 Influence of disease location on vedolizumab efficacy in inflammatory bowel disease: a real-life multicentre experience. (16th January 2018) - Pestour, S; Nancey, S; Charlois, A L; Bonaz, B; Flourie, B; Boschetti, G; Mathieu, N
Abstract: Background: The influence of inflammatory bowel disease (IBD) location on vedolizumab efficacy is unclear. Our goal was to determine whether IBD location has an influence on the rate of steroid-free clinical remission (SFCR) at week 24 under vedolizumab. Methods: We included in a retrospective multicentre study all consecutive patients with moderate to severe Crohn's disease (CD) or ulcerative colitis (UC) receiving vedolizumab from 2014 to 2017. SFCR was assessed at week 24 and defined by a Harvey-Bradshaw Index (HBI) ≤ 4 for CD or a Partial Mayo Score (PMS) ≤ 2 with each sub-score of 0 or 1 for UC and corticosteroid withdrawn for at least 1 month. The disease location was defined according to the Montreal classification and assessed by endoscopy and imagery. Active perianal CD was defined as simple or complex perianal fistula and/or ulcerations. Results: Two hundred and twenty-three IBD patients were included: 133 CD patients (75 females, mean age 38 years) and 90 UC patients (47 females, mean age 43 years). The mean disease duration in CD patients was 14.2 ± 0.9 years and in UC patients 8.7 ± 0.8 years. Seventy-two CD patients (54%) had undergone an intestinal resection. The majority of patients (98% of CD patients and 95% of UC patients) had previously received at least one line of anti-TNF therapy. Isolated ileal location (L1), isolated colonic location (L2) and ileocolonic location (L3) represented respectively 22%, 11%, and 67% of CD patients, and active perianal CD was reported at week 0 in 29 patients (22%). Proctitis (E1), left sided colitis (E2), and extensive disease (E3) were reported in 3%, 31%, and 66% of UC patients. All patients received an intravenous infusion of 300 mg vedolizumab at weeks 0, 2, 6 (induction regimen) and then once every 4 or 8 weeks thereafter (maintenance regimen). SFCR was achieved in 33.1% ( n = 44/133) CD patients and 33.3% ( n = 30/90) UC patients at week 24. SFCR rates for CD were 33%, 36% and 35%, respectively for L1, L2, and L3 disease locations ( p = 0.906), with no difference when L2 disease was compared with ileal disease (L1 and L3) ( p = 0.928). SFCR at week 24 was achieved in 17% of CD patients with active perianal disease at week 0 vs. 42% of CD patients without active perianal disease at week 0 ( p = 0.037). SFCR rates for UC were 37% and 31%, respectively for distal UC (E1, E2) and pancolitis (E3) ( p = 0.594). Failure to obtain clinical remission at week 14 was associated with failure to achieve SFCR at week 24. Conclusions: Vedolizumab efficacy was not influenced by IBD location, except for perianal CD since an active perianal CD at week 0 was associated with a lower probability to obtain SFCR at week 24. A prospective study is required to confirm these results.